Replacing water and nutrients for ethanol production by ARTP derived biogas slurry tolerant Zymomonas mobilis strain - Guowei Duan; Bo Wu; Han Qin; Weiting Wang; Qiong Tan; Yonghua Dai; Yao Qin; Furong Tan; Guoquan Hu; Mingxiong He (Biotechnology for Biofuels, 2019)
Abstract Background Reducing fresh water consumption and nutrient addition will be an effective way to reduce the whole cost of bioethanol production. On the other hand, treatment of biogas slurry derived from anaerobic digestion (AD), in which a great amount of nutrients is still left, costs too much to remove these pollutants. It would be beneficial for both digestate valorization and ethanol production if biogas slurry is used for producing bioethanol. However, both hyperosmosis and potential biotoxic components of the biogas slurry can severely inhibit fermentation. Results In this study, two rounds of atmospheric and room temperature plasma (ARTP) mutagenesis combined with adaptive laboratory evolution (ALE) were applied to improve the adaptability and genetic stability of Zymomonas mobilis in biogas slurry. Mutants D95 and S912 were identified. Growth of the mutants was remarkably improved in biogas slurry. The highest ethanol productivity reached 0.63 g/L/h which was 61.7% higher than ZM4 (0.39 g/L/h). Genomic re-sequencing results also revealed that single nucleic variations (SNVs) and Indels occurred in the mutants, which are likely related to inhibitor in biogas slurry and low pH tolerance. Conclusions Our study demonstrated that these mutant strains have great potential to produce ethanol using biogas slurry to replace fresh water and nutrients.